CHI-KAT8i5 suppresses ESCC tumor growth by inhibiting KAT8-mediated c-Myc stability - Dandan Zhang; Ming Jiang; Pan Li; Kyle Vaughn Laster; Dengyun Zhao; Yafei Zhi; Huifang Wei; Wenna Nie; Yunfeng Gao; Qiong Wu; Pu Xiang; Xinyu He; et al. (Cell Reports)
Summary: The integrated analysis of histone modifier enzymes in solid tumors, especially in esophageal squamous cell carcinoma (ESCC), is still inadequate. Here, we investigate the expression levels of histone modifier enzymes in ESCC tissues. Notably, KAT8 (lysine acetyltransferase 8) is identified as a prognostic and therapeutic biomarker in ESCC. Esophageal-tissue-specific deletion of KAT8 in mice led to less tumor burden after induction of tumorigenesis via 4-nitroquinoline N-oxide (4NQO) treatment compared with wild-type mice. Meanwhile, silencing KAT8 significantly suppresses tumor growth in cell-line-derived xenograft (CDX) and patient-derived xenograft (PDX) models. Mechanically, we confirm that KAT8 regulates c-Myc protein stability by directly binding it. Furthermore, we design and screen a specific KAT8 inhibitor (CHI-KAT8i5) that significantly attenuates tumor growth in vitro and in vivo, providing promising potential for clinical application. Thus, our work identifies that KAT8 could serve as a potential clinically relevant biomarker and therapeutic target in patients with ESCC and that KAT8 inhibitor is a promising lead candidate for ESCC therapy.